2009
DOI: 10.1302/0301-620x.91b8.22129
|View full text |Cite
|
Sign up to set email alerts
|

The impact of obesity on the mid-term outcome of cementless total knee replacement

Abstract: We evaluated 535 consecutive primary cementless total knee replacements (TKR). The mean follow-up was 9.2 years (0.3 to 12.9) and information on implant survival was available for all patients. Patients were divided into two groups: 153 obese patients (BMI > or = 30) and 382 non-obese (BMI < 30). A case-matched study was performed on the clinical and radiological outcome, comparing 50 knees in each group. We found significantly lower mean improvements in the clinical score (p = 0.044) and lower post-operative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
3

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 30 publications
0
33
0
3
Order By: Relevance
“…Foran et al (19) concluded in their study with 87 knees that any degree of obesity has a negative impact on the outcome of TKA: they found that there was a significant difference in the postoperative Knee Society scores between non-obese and obese patients. Jackson et al (20) reported that obese patients had significantly lower mean improvement in clinical scores after TKA measured by using The Hospital for Special Surgery Knee Rating Score system (HSS). Obesity has also been shown to increase the risk of postoperative complications after knee replacement surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Foran et al (19) concluded in their study with 87 knees that any degree of obesity has a negative impact on the outcome of TKA: they found that there was a significant difference in the postoperative Knee Society scores between non-obese and obese patients. Jackson et al (20) reported that obese patients had significantly lower mean improvement in clinical scores after TKA measured by using The Hospital for Special Surgery Knee Rating Score system (HSS). Obesity has also been shown to increase the risk of postoperative complications after knee replacement surgery.…”
Section: Discussionmentioning
confidence: 99%
“…For most obese patients, as for any patient, TKA results in improved pain and function scores with high satisfaction rates [2,12,26,30,33,37,49]. MBT components and modern APT components both have been shown to be successful in the general population; however, the use of APT components specifically in obese patients has not been well studied.…”
Section: Discussionmentioning
confidence: 99%
“…Studies focusing on the obese patient population show most patients show improvements in outcome scores and are satisfied with TKA [1,2,12,18,19,24,26,30,33,37,43,44,48,49]. However, high body weight amplifies the magnitude of joint load per step and may adversely affect polyethylene wear performance and the rate of aseptic loosening.…”
Section: Introductionmentioning
confidence: 99%
“…After consensus was reached, twenty studies were included for data analysis. The baseline characteristics and methodology of the included trials are summarized in the Appendix [6][7][8][9][10][11][12][13][14][15][16][22][23][24][25][26][27][28][29][30] . Data regarding the presence of any infection were extracted from the studies in which this outcome was reported; in addition, deep and superficial infections were analyzed separately in studies Flowchart showing identification of the included studies.…”
mentioning
confidence: 99%